HYDROGEOLOGICAL ACTION OF DRAINAGE AND DRAINAGE SYSTEMS OF POLISSІA ZONE IN CHANGING CLIMATIC CONDITIONS - Rokochinskiy, A.; Shevchenko, O.; Volk, P.; Turchenyuk, V.; Koptjuk, R.; Volk, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
We have analyzed various methods and models for determining and calculating drainage module. The drainage module is an important indicator of the hydrogeological effect of drainage and soil drainage. For the calculation of the drainage calculation module, an empirical, analytical, water-balance method is used, or it is accepted on the recommendations without sufficient economic and environmental justification. This does not meet the modern requirements for the creation and operation of such objects. Traditionally, the designs and parameters of agricultural drainage are determined by the drainage module. It provides the necessary conditions for the removal of excess moisture of the active soil layer in the spring (as the main calculation) and corresponds to a certain level of the calculated security of the formation of the runoff hydrograph. According to the generalized results of the research, in the calculation of drainage parameters, the values of drainage modules were taken within: for mineral soils – 0.4… 0.6 l/sꞏha, for peat soils 0.2… 0.6 l/sꞏha. These recommended values are not correct because then the defined drainage parameters take into account only the technological conditions of its operation. But this does not take into account the conditions of formation of economic and environmental effect within the system, and they are not economically and environmentally optimal for the calculation of the drainage system and its elements. We have performed research and evaluation of the hydrogeological effect of the drainage and drainage systems. The results of these researches showed the variability of values of drainage modules in time and space. We have also identified many influencing factors and confirmed their difference with the calculated value. A new evaluation of the effectiveness of drainage systems and the calculation of drainage modules are proposed. This evaluation includes the yield criterion for variable natural (climatic) and agricultural conditions. New optimal values of drainage modules are proposed. These values are also presented for critical conditions (maximum daily rainfall of different levels of probability).
Keywords: hydrogeological action of drainage; drainage systems; changing climatic conditions